INCORPORATING FOREIGN LANGUAGE WORDS IN RESEARCH WRITING - Urazbaeva Dilbar Turdibayevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation:  This article explores the role and impact of incorporating foreign language words in academic research writing. The practice enriches vocabulary, reflects cultural diversity, and provides precise terminology in fields like linguistics, anthropology, and social sciences. However, integrating foreign words also brings challenges related to readability and standardization. This study examines the reasons, methodologies, and effects of foreign language word use in research writing across multiple disciplines, offering insights and best practices for researchers.